CERTAIN LEGAL ASPECTS OF A PROFESSIONAL ATHLETE'S CONTRACT - Musayev Elbek Tayufovich (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to analyze the legal framework governing sports contracts in Uzbekistan, identify challenges in the current regulations, and propose recommendations for improvement, focusing on the classification of sports contracts as labor, civil-law, or hybrid agreements. Method: A comparative legal analysis was conducted, examining national and international legal frameworks, including Uzbekistan’s legislation, the Civil Code of Belarus, and labor regulations in Germany, Mexico, and Chile. A doctrinal approach was employed to explore legal debates on the classification of sports contracts. Results: The findings reveal that sports contracts occupy a unique legal space, blending elements of labor and civil-law agreements. In Uzbekistan, ambiguities persist in the “Law on Physical Culture and Sports,” which does not explicitly favor labor or civil-law contracts. By contrast, countries like Belarus explicitly recognize hybrid contracts, offering greater flexibility. Comparative analysis highlights that countries like Italy and Spain, which integrate sports-specific legislation with general labor laws, provide a balanced approach. These frameworks could serve as models for Uzbekistan. Novelty: This research contributes to the discussion by proposing the adoption of hybrid contracts as a solution to legal ambiguities. Hybrid contracts can balance the operational flexibility required by sports organizations with the social protections necessary for athletes, aligning Uzbekistan’s regulations with international best practices.